Survei Pemahaman Konsep Siswa Kelas XII SMA Pada Materi Glb Dan Glbb - Natalia Hutahaean (Al-Khazini, 2024)
This research is qualitative research and the instrument in this research is a questionnaire containing statement questions about understanding the concept of GLB and GLBB material. This research aims to determine the understanding of physics concepts in class XII IPA at SMA Negeri 14 Medan on GLB and GLBB material. Based on the results of the research and discussion, it can be concluded that the understanding of physics concepts in class